Tau pathology-mediated presynaptic dysfunction. (14th June 2016) - Moreno, H.; Morfini, G.; Buitrago, L.; Ujlaki, G.; Choi, S.; Yu, E.; Moreira, J.E.; Avila, J.; Brady, S.T.; Pant, H.; Sugimori, M.; Llinás, R.R.
Highlights: htau42 in the presynaptic terminal induces calcium release from the ER. The acute-modulation of IP3R and RyR by tau protein (directly or indirectly). Identification of a synaptotoxic-tau region (PAD). The modulation of downstream kinases by PAD. Abstract: Brain tauopathies are characterized by abnormal processing of tau protein. While somatodendritic tau mislocalization has attracted considerable attention in tauopathies, the role of tau pathology in axonal transport, connectivity and related dysfunctions remains obscure. We have previously shown using the squid giant synapse that presynaptic microinjection of recombinant human tau protein (htau42) results in failure of synaptic transmission. Here, we evaluated molecular mechanisms mediating this effect. Thus, the initial event, observed after htau42 presynaptic injection, was an increase in transmitter release. This event was mediated by calcium release from intracellular stores and was followed by a reduction in evoked transmitter release. The effect of htau42 on synaptic transmission was recapitulated by a peptide comprising the phosphatase-activating domain of tau, suggesting activation of phosphotransferases. Accordingly, findings indicated that htau42-mediated toxicity involves the activities of both GSK3 and Cdk5 kinases.